Anti-fungal capacity of Saga leaf (Abrus Precatorius L) towards Candida Albicans testing - NA, Muslim Paranto; Harjadinata, Karlina; Dewi, Warta (Padjadjaran Journal of Dentistry, 2007)
The aim of this study was to evaluate the antifungal effect, by determining the Minimum Inhibitory Concentration (MIC) of saga leave extract against Candida albicans, as a causal of oral candidiasis. The saga left was extracted following maceration method. Candida albicans, as a tested fungal was isolated from patients at the Oral and Dental Hospital Faculty of Dentistry Universitas Padjadjaran. They were cultured on Sabouraud Agar plate, incubated at 37°C for 18-24 hours. The isolation and the identification of Candida albicans were based on colonial morphology and the fermentation of glucose, maltose, saccharose, dan lactose at the Microbiology Laboratory. This experimental laboratory study was conducted according to a serial dilution method from 16 mg/ml up to 0,25 mg/ml of saga leave extract with two-fold dilution in three repetitions. The result showed that the Saga leaves extract to be able to inhibit Candida albicans at minimum 2 mg/ml concentration. As a conclusion, the concentration of 2 mg/ml or more of saga leave extract has antifungal effect against Candida albicans.